Two Cases of Anterior Shoulder Dislocation and Fracture Secondary to Generalized Tonic-Clonic Seizure - Kevin Trong Dao; Hari Kunhi Prasad Veedu; Britney Ly; Neela Zalmay; Rajashree Hariprasad; Michael Eagan; Najib Ussef (Case Reports in Orthopedics)
Dislocation of the glenohumeral joint secondary to generalized tonic-clonic seizures is well documented in the medical literature, with posterior dislocation being most commonly described. Still, these occurrences tend to be rare and affect a minority of patients, and fractures associated with dislocations after seizures are even less common. As such, the management of these injuries tends to be quite varied, and there is a paucity of documented cases in the literature. Here, we would like to present two rare cases of anterior shoulder dislocation secondary to seizures, with one patient also sustaining a fracture of the proximal humerus. We would also like to discuss the management and outcomes that have been achieved, since these cases tend to occur in a small number of epileptic patients.